Changes in Spatiotemporal Variability of Muscular Response Under the Influence of Post-Stroke Spasticity - Tian Xie; Yan Leng; Ruxin He; Chuhuai Wang; Rong Song (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Spasticity is characterized by involuntary muscle activation due to the hyperexcitability of the stretch reflex. However, the temporal pattern and spatial heterogeneity of motor unit recruitment in this activation are not fully understood. The aim of this study was to investigate changes in spatiotemporal variability in spastic muscle responses to passive stretch after stroke. We acquired high-density surface electromyography (HD-sEMG) signals from the biceps brachii in 21 stroke survivors, 10 age-matched old healthy controls, and 10 young healthy controls at velocities of 10°/s, 60°/s, 120°/s, and 180°/s. The average and distribution of fuzzy entropy extracted from HD-sEMG signals were used to characterize the spatiotemporal variability of muscle activation. Our results showed that the temporal variability of stroke survivors was significantly lower than that of old controls, while the latter was significantly lower than that of young controls. As velocity increased, only stroke survivors showed decreased activation variability and increased activation levels in specific region, and the distributions were similar across velocities. Notably, the activation variability and the size of regions with high activation levels were significantly negatively and positively correlated with the severity of spasticity, respectively. These findings provide entropy-based evidence for the contribution of greater silencing of motoneurons responsible for reflex inhibition to the synchronous recruitment of more motor units.